OS DISCURSOS DE TRABALHADORES AUTOGESTIONÁRIOS - Webber, Darlene Arlete (Organon, 2010)
The analysis of the discourse practices of workers who constitute and enable cooperatives organizations of auto management belonging to the Solidary Economy in Rio Grande do Sul appears with the main objective in this approach. It is about undertaking of industrial production in the auto management model, created from the bankruptcy of capitalist management enterprises. The study deals with the observation of the discourse process of the practices of auto managing subjects, of auto management supporters and of working class intellectuals, in this process ideas and beliefs are “disarranged”, “rearranged” and “transformed” of non linear way. This new social and discourse practices of the auto managing organization of workers can be found in different moments of the humanity history, which leads us to think about the discourse resonances and interdiscourse connections.